Oil price shocks, fuel subsidies and macroeconomic (in)stability in Nigeria - Babatunde S. Omotosho (CBN Journal of Applied Statistics, 2019)
This paper studies the macroeconomic implications of oil price shocks and the extant fuel subsidy regime for Nigeria. To do this, we develop and estimate a New-Keynesian DSGE model that accounts for pass-through effect of international oil price into the retail price of fuel. Our results show that oil price shocks generate significant and persistent impacts on output, accounting for about 22 percent of its variations up to the fourth year. Under our benchmark model (i.e. with fuel subsidies), we show that a negative oil price shock contracts aggregate GDP, boosts non-oil GDP, increases headline inflation, and depreciates the exchange rate. However, results generated under the model without fuel subsidies indicate that the contractionary effect of a negative oil price shock on aggregate GDP is moderated, headline inflation decreases, while the exchange rate depreciates more in the short-run. Counterfactual simulations also reveal that fuel subsidy removal leads to higher macroeconomic instabilities and generates non-trivial implications for the response of monetary policy to an oil price shock. Thus, this study cautions that a successful fuel subsidy reform must necessarily encompass the deployment of well-targeted safety nets as well as the evolution of sustainable adjustment mechanisms.
Keywords: E31; E32; E52; E62; 330; Fuel subsidies; Oil price shocks; Oil price pass-through